Changes in pH and Nitrite Nitrogen Induces an Imbalance in the Oxidative Defenses of the Spotted Babylon (Babylonia areolata) - Ruixia Ding; Rui Yang; Zhengyi Fu; Wang Zhao; Minghao Li; Gang Yu; Zhenhua Ma; Humin Zong (MDPI AG, 2023)
In order to reveal the acute toxicity and physiological changes of the spotted babylon (Babylonia areolata) in response to environmental manipulation, the spotted babylon was exposed to three pH levels (7.0, 8.0 and 9.0) of seawater and four concentrations of nitrite nitrogen (0.02, 2.7, 13.5 and 27 mg/L). The activities of six immunoenzymes, superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), catalase (CAT), acid phosphatase (ACP), alkaline phosphatase (AKP) and peroxidase (POD), were measured. The levels of pH and nitrite nitrogen concentrations significantly impacted immunoenzyme activity over time. After the acute stress of pH and nitrite nitrogen, the spotted babylon appeared to be unresponsive to external stimuli, exhibited decreased vigor, slowly climbed the wall, sank to the tank and could not stand upright. As time elapsed, with the extension of time, the spotted babylon showed a trend of increasing and then decreasing ACP, AKP, CAT and SOD activities in order to adapt to the mutated environment and improve its immunity. In contrast, POD and GSH-PX activities showed a decrease followed by an increase with time. This study explored the tolerance range of the spotted babylon to pH, nitrite nitrogen, and time, proving that external stimuli activate the body's immune response. The body's immune function has a specific range of adaptation to the environment over time. Once the body's immune system was insufficient to adapt to this range, the immune system collapsed and the snail gradually died off. This study has discovered the suitable pH and nitrite nitrogen ranges for the culture of the spotted babylon, and provides useful information on the response of the snail's immune system.